2016
DOI: 10.1371/journal.pntd.0005041
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy Drug Resistance Surveillance in Colombia: The Experience of a Sentinel Country

Abstract: An active search for Mycobacterium leprae drug resistance was carried out, 243 multibacillary patients from endemic regions of Colombia were included from 2004 to 2013 in a surveillance program. This program was a World Health Organization initiative for drug resistance surveillance in leprosy, where Colombia is a sentinel country. M. leprae DNA from slit skin smear and/or skin biopsy samples was amplified and sequenced to identify mutations in the drug resistance determining region (DRDR) in rpoB, folP1, gyrA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 24 publications
3
28
1
2
Order By: Relevance
“…Finally, none of these studies reported antibiotic resistance pattern of M. leprae. There are reports on drug resistance in leprosy patients [45][46][47][48][49] and can be one of the reasons of the relapse rate increase in the last years [50]. Considering some of the areas with leprosy had also high incidence of resistant tuberculosis (such us India) and MDT share rifampin as an important drug with sensitive tuberculosis, closer follow-up and drug resistance studies should be done in these areas.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Finally, none of these studies reported antibiotic resistance pattern of M. leprae. There are reports on drug resistance in leprosy patients [45][46][47][48][49] and can be one of the reasons of the relapse rate increase in the last years [50]. Considering some of the areas with leprosy had also high incidence of resistant tuberculosis (such us India) and MDT share rifampin as an important drug with sensitive tuberculosis, closer follow-up and drug resistance studies should be done in these areas.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Nevertheless, no effective BI change was observed in some leprosy cases, even if MDT was prescribed for more than 1-year (Supplementary Table 1) [10–19]. The factors influencing the lack of BI decline remain unknown, but high initial BI and no decline in BI at RFT are possible signs of AMR [12].…”
Section: Introductionmentioning
confidence: 99%
“…Non-cured individuals, apart from contributing to continuing transmission, can develop permanent physical disabilities, reactional states and drug resistance. 26,27 The second piece of evidence relates to the percentage of contacts examined. This is an indicator of the capacity of health services to undertake surveillance of case contacts and thus increase timely detection of new cases.…”
Section: Discussionmentioning
confidence: 99%
“…3 Currently, in addition to being in first place in terms of prevalence (1.10/10,000 inhab. in 2016), Brazil is in second place after India with regard to the absolute number of new cases. In 2016 alone, 25,218 new leprosy cases were diagnosed in Brazil, 1,696 of which occurred in people under 15 years old.…”
Section: Introductionmentioning
confidence: 99%